Hyperammonemia in a carbamoyl-phosphate synthetase 1 deficiency recipient after living-donor liver transplantation from a carrier donor: a case report - Kakiuchi, Toshihiko; Nosho, Tetsuya; Oka, Masafumi; Tashiro, Katsuya (Frontiers in Medicine, 2024)
Carbamoyl-phosphate synthetase 1 (CPS1) deficiency is an autosomal recessive congenital urea cycle disorder (UCD) characterized by hyperammonemia. The recipients of liver transplantation (LT) for UCD are often children, and the potential donors are often the parents. Hereditary congenital diseases involving UCD entail the possibility of both parents being genetically heterozygous. Herein, we describe the case of a 12-year-old girl with CPS1 deficiency receiving a liver transplant (soon after birth) from her father, who had a heterozygous CPS1 mutation. She was referred to our hospital with respiratory distress after contracting two infections (respiratory syncytial virus and human metapneumovirus) within a short period, both of which presented with hyperammonemia. Medication for hyperammonemia quickly lowered the ammonia levels. The hyperammonemia was thought to be caused by the heterozygous mutation in the donor liver; moreover, it is likely that the low enzyme activity in the patient’s liver was increased due to the infections. This is the first study to report hyperammonemia in a CPS1 deficiency patient due to an infection after LT. Thus, patients with CPS1 deficiency should be aware of the development of hyperammonemia after LT.